The Student’s Lack Of Interest In Efl Reading Classroom - Rowa, Monika (Journal of Literature Language and Academic Studies, 2022)
This study aims to determine the low interest in learning of students towards the subject of "Reading" class VII SMP Negeri 2 Gamping. This type of research is a qualitative descriptive research. The subjects of this study were students of class VII F of SMP Negeri 2 Gamping. Data collection techniques used interview tests and documentation as many as 32 subjects with the criteria of each student being in the high, medium, and low categories. The data analysis technique used is descriptive qualitative method, which describes the data collected in the form of words, pictures and not numbers. The results showed that students who had an interest in reading at a low level of interest in reading English as a foreign language in a class in the high category were students who had a habit of reading and had an interest in reading. Students' abilities in the medium category are students who lack interest in reading and students' reading abilities in the low category are students who do not have interest in reading.